The dialectics of invisibilization in Syrian female refugees in Turkey - Yamaner, Onur (2021)
This article deals with how Syrian female refugees are intersectionally invisibilized in Turkey as refugees and as women. The main aim of this study is to understand the dialectics of (in)visibilization of Syrian female refugees. Therefore, using Critical Discourse Analysis (CDA), we analysed discourses in social media as well as popular discourses by Turkish and Syrian women in Ankara. We concentrate on the relation between the discourses produced in the host society and the particular way of how Syrian female refugees are portrayed and invisibilized. We wanted to know how powerful these discourses are in the host society when it comes to the (in)visibilization of Syrian women and their bodies. Furthermore, we wanted to understand the intersectionality of discrimination and invisibilization of Syrian female refugees. This study shows how discriminatory discourses are internalized and circulate also among women. Moreover, we show how different forms of invisibilization are usually related to marginalization, but in some cases can even be used as a means to escape discrimination.